TRUST AND ECONOMIC SATISFACTION AS ANTECEDENTS, AND LOYALTY AS OUTCOME, OF SMALL BUSINESS CUSTOMERS’ COOPERATION AND COORDINATION IN BANKING RELATIONSHIPS - Russell KAMPANI; Pierre MOSTERT; Michelle Caroline VAN DER MERWE (Management & Marketing)
Business success is determined by the ability to establish stable relationships that result in the retention of loyal customers. Extant literature on business-to-business relationships highlights trust, satisfaction, cooperation, and coordination, regarded as important constructs comprising relationship quality (RQ), as key drivers for ensuring loyalty. However, the interaction between these RQ constructs remain unclear. This study accordingly investigates a framework where trust and economic satisfaction are antecedents of cooperation and coordination, which ultimately influence small business customers’ loyalty towards their banks. The sample comprised 269 small businesses operating in South Africa. The empirical findings of this study show that trust and economic satisfaction within banking relationships are significant predictors of cooperation and coordination, which in turn positively influences small business customers’ loyalty towards their banks. This study contributes to existing literature by incorporating a small business banking perspective investigating the interrelatedness of selected constructs on establishing stable relationship and customer loyalty.